Pengaruh Pendapatan Dari Biaya Operasional Terhadap Laba Bersih (Studi Kasus Pada Perusahaan Manufaktur Sektor Keramik Porselin dan Kaca yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016) - Fuji Nurhidayati Usman; Solihin Sidik (Peneliti.net, 2023)
Operational costs are costs incurred by the company in carrying out its business activities. Operational costs greatly influence decisions that support the success of company goals. Revenue is income from the company's main operating activities, such as trading and owner's equity in the sales activities of manufacturing companies. The purpose of this study is to analyze the effect of income from operating expenses on net income. The method used in this research is quantitative method. From the results of the study it can be concluded that this study shows that partially income has an effect of 0.262 on net profit in manufacturing companies in the basic industrial and chemical sectors listed on the IDX for the period 2012 to 2016. The company's net profit will increase by 0.262 if its income increases by 1.